Vitamin D and the Pathogenesis of Primary Hypothyroidism - Jebur , Abbas S; Saleh, Basil O.; Al Azzawi, Omar F. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Vitamin D deficiency is a risk factor for neuropsychiatric disorders and autoimmune diseases. Objectives: This study aimed to investigate the relationship between vitamin D and the pathogenesis of primary hypothyroidism. Methods: A case-control study was conducted at the Department of Biochemistry, College of Medicine, University of Baghdad, and Endocrinology and Diabetes Clinic. The study involved 81 patients aged 29-62 years, with 24 newly diagnosed hypothyroidism, 33 had established hypothyroidism, and 24 had subclinical hypothyroidism. The control group consisted of 40 healthy individuals aged 29-62 years. The study used the MAGLUMI® 800 analyzer Chemiluminescence Immunoassay System, which uses Acridinium Ester-based Immunoassay technology for high sensitivity and specificity (True Negative Rate). Thyroid peroxidase antibodies and 25- hydroxyvitamin D were also tested using the Enzyme-Linked Immunosorbent Assay technique. Results: The results revealed that the median and 1st -3rd quartile range values of serum 25 hydroxyvitamin D levels of newly diagnosed, established, and subclinical primary hypothyroidism were significantly decreased compared to controls (for all, p<0.0001). However, there were non-significant differences between newly diagnosed and subclinical, newly diagnosed and established, and between subclinical and established. There was a significant negative correlation between 25-hydroxyvitamin D and thyroid stimulating hormone in newly diagnosed and significant positive correlation in subclinical. Also, there were significant positive correlations between 25-hydroxyvitamin D and freeT4 in established and subclinical. Conclusion: Vitamin D deficiency may play an important role in the pathogenesis of primary hypothyroidism, whether it is a newly diagnosed, established, or subclinical one.